Translation and validation of the Korean version of the Diabetic Foot Ulcer Scale‐Short Form - Lee, Ye‐Na (Int Wound J, 2019)
The purpose of this study was to translate the Diabetic Foot Ulcer Scale‐Short Form (DFS‐SF) into Korean and evaluate its psychometric performance in patients with diabetic foot ulcers (DFUs). The DFS‐SF was translated into Korean using translation guidelines from the World Health Organization. The Korean version of DFS‐SF (DFS‐SF‐K) went through the full linguistic validation process and was evaluated in 320 Korean patients with DFU. For this study, Cronbach's alpha was used to evaluate the reliability of the DFS‐SF‐K. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and known‐group validity were conducted to examine construct validity. Correlation of the DFS‐SF‐K with SF‐36 was used to test concurrent validity of the DFS‐SF‐K. Cronbach's alpha was >0.70 for all scales. Factor loadings of the 29 items on the six subscales ranged from 0.82 to 0.95. The six‐subscale model was validated by CFA (x (2)/df = 4.55, P < 0.001, RMR = 0.06, GFI = 0.73, NFI = 0.90, TLI = 0.91, CFI = 0.92, RMSEA = 0.10). Spearman's correlations and known‐groups comparisons supported construct validity. The newly translated DFS‐SF‐K may be used to assess the impact of QoL with DFUs in Korean patients.